Instruction in Co-Taught Secondary Classrooms: An Exploratory Case Study in Algebra 1 - Weiss, Margaret P.; Rodgers, Wendy (Journal of the American Academy of Special Education Professionals, 2020)
Co-teaching is a widely-used service delivery model to support students with disabilities in accessing the general curriculum in the United States. The pairing of a special educator and general educator is meant to produce substantively different instruction than when the general educator teaches alone. Research into these instructional differences is still scarce. In this exploratory case study, we compare the instruction of a co-taught Algebra 1 Part 1 class to the instruction in an Algebra 1 Part 1 class taught by the same math educator alone in a rural high school, including grades nine through twelve. Few instructional differences were found. Implications of our findings and ideas for future research are discussed.